Dielectric and ferroelectric properties of samarium substituted BaBi4Ti4O15 Aurivillius oxides. Issue 7 (15th May 2016) - Reddyprakash, M.; Rout, S.K.; Satapathy, Avishek; Sinha, T.P.; Sariful, S. Md.
Abstract: Barium bismuth titanate ceramics doped with different concentration of samarium Ba 1 − ( 3 / 2 ) x Sm x Bi 4 Ti 4 O 15, ( x =0, 0.05, 0.10, 0.20, 0.30, and 0.40) were prepared by solid state reaction route. X-ray diffraction pattern confirmed that all compositions have a bismuth- layered perovskite structure with an orthorhombic phase of space group A2 1 am . The plate-like grain morphology was observed for the compositions upto ( x =0, 0.05, and 0.10) and the shape changed for higher samarium ( Sm 3 + ) concentration. FT-IR study confirmed the presence of Bi–O stretching vibrations. The temperature dependent dielectric behavior showed a frequency dependent diffused phase transition above 400 °C and a broadening of phase transition with increasing Sm 3 + content. The phase transition temperature shifted to higher temperatures with increasing Sm 3 + content. Ferroelectric studies revealed that the remanent polarization ( P r ) first increased, and then decreased with rising in dopant concentration. The maximum value of remanent polarization ( P r ) was found to be 2.40 μC / cm 2 for x = 0.05 composition at an applied electric field of 80 kV/cm.